Characteristics and Outcome in Children With Craniectomy Following Acute Ischemic Stroke in the International Pediatric Stroke Study. (October 2019) - Lehman, Laura L.; DeVeber, Gabrielle; Pergami, Paola; Guilliams, Kristin P.; Chung, Melissa; Felling, Ryan; Dowling, Michael M.; Rivkin, Michael J.
The outcome of children with acute ischemic stroke treated with craniectomy has not been thoroughly examined. In adults, hemicraniectomy after middle cerebral artery territory stroke and posterior decompression after posterior circulation stroke has been shown to improve outcome. Pediatric cases of hemicraniectomy for middle cerebral artery stroke and posterior decompression following posterior circulation stroke suggest relatively good outcome. There are no published data in adults or children with craniectomy after cerebral sinovenous thrombosis. Our aim was to determine the outcome of children with acute ischemic stroke treated with craniectomy in the International Pediatric Stroke Study (IPSS). We included children enrolled who had a craniectomy following stroke presentation. Of 4294 patients in IPSS, 38 children (1%) were found to have craniectomy following an ischemic stroke. Of 38 craniectomy cases, 29 had anterior circulation strokes, 5 had posterior circulation strokes, and 4 had cerebral sinovenous thromboses. The mortality rate was 8%. Overall, children who have craniectomies have significant neurologic deficits. Prospective studies are needed to examine long-term morbidity following craniectomy.